Mdm Halimah Yacob graces SMU Patron’s Day 2018 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
SMU powered up to celebrate its 18th Patron’s Day (PD18) on 26 January and to welcome Singapore President Madam Halimah Yacob, on her inaugural visit as SMU’s third Patron.